Internalization of Pasang Ri Kajang in Islamic Character Education of the Ammatoa Kajang Indigenous People - Najiah, Didi Firqatun Najiah; Afriandi, Afriandi; Ulum, Fathul; Sunalti, Esi; Adrian, Egi; Anugrah, Fadil (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
This study explores the process of internalizing the values of Pasang Ri Kajang within the informal education system of the Ammatoa Kajang indigenous community in Bulukumba, South Sulawesi. Pasang RI Kajang is a revered oral tradition that serves as a comprehensive life guide encompassing social, spiritual, and environmental ethics. Core values such as kamase-masea (simplicity), kalambusang (honesty), and adherence to customary law are integrated into all aspects of daily life. Utilizing a descriptive qualitative approach, data were collected through semi-structured interviews with a key informant from the Kajang community who had pursued formal education outside the traditional region. The findings reveal that character education within the Kajang community is shaped through daily practices, role modeling, and active participation in customary rituals. The four paired values of Tuoki’na Kamase-masea which emphasize simplicity in sitting, speaking, walking, and dressing form the foundation for youth character development. The community maintains social equality by symbolic practices such as not using chairs inside homes, enforcing verbal discipline through social fines for harsh language, and prohibiting footwear as a sign of respect toward the earth. These values not only shape individual behavior but also reinforce collective identity and ecological awareness. This study highlights that indigenous education based on local wisdom plays a significant role in preserving cultural values, fostering character development, and promoting environmental stewardship in the context of modern education